Paguyuban “Tuk Bebeng” and Community Strength-Based Water Management in Disaster-Prone Areas of Merapi, Yogyakarta - Prayoga, Reza Amarta; Wahyono, Eko; Fatimah, Siti; Purbandini, Lis; Wibowo, Djoko Puguh (Jurnal Kawistara, 2024)
Water management in disaster-prone areas such as Merapi often creates various social vulnerabilities such as social conflicts, poverty and weakened role of local organizations. The exclusion of the role of local organizations in community-based water management is often overlooked. A local community organization called Tuk Bebeng that work on water management in the sloop of the Merapi volacne in Yogyakarta is an example of such an overlooked role of an important actor in disasterprone areas. This paper aims to examine the strength the Tuk Bebeng Association in water management in disaster-prone areas of Merapi. This research is basedon a descriptive qualitative method with data collection through field observations, in-depth interviews, and focused discussion forums. The results of the study show that the Tuk Bebeng Association has played important roles in eliminating various sectoral conflicts of interest.This good practice is carried out through the strong base of the community’s collectivity which manifest in two forms including mechanical solidarity and moral rationality. Through these roels the Tuk Bebeng community serves as guardians of the balance of harmony between nature and society. The pattern of life of the people around Merapi, namely Se omah, Guyub, dan se-rahim(common home, harmony, and the same homeland), as the glue of brotherhood can act as a damper for anger and compromise in the cross-linking of interests in water management. The practical implications of this research offer realistic practices to reduce the cross- interest (conflict) that occurs by providing space for important actors managing Tuk Bebeng to dialogue equally, and empowering the underrepresented Paguyuban Bebeng actors with legal formal and cultural recognition that Tuk Bebeng belongs to the Merapi community. Theoretical implications show that rationality and solidarity theories have a strong relationship in mobilising collective action in communities in disaster-prone areas.